An ex vivo Approach to Study Hormonal Control of Spermatogenesis in the Teleost Oreochromis niloticus - Thönnes, Michelle; Vogt, Marlen; Steinborn, Katja; Hausken, Krist N.; Levavi-Sivan, Berta; Froschauer, Alexander; Pfennig, Frank (Frontiers in Endocrinology, 2020)
As the male reproductive organ, the main task of the testis is the production of fertile, haploid spermatozoa. This process, named spermatogenesis, starts with spermatogonial stem cells, which undergo a species-specific number of mitotic divisions until starting meiosis and further morphological maturation. The pituitary gonadotropins, luteinizing hormone and follicle stimulating hormone, are indispensable for vertebrate spermatogenesis, but we are still far from fully understanding the complex regulatory networks involved in this process. Therefore, we developed an ex vivo testis cultivation system which allows evaluating the occurring changes in histology and gene expression after gonadotropin treatment. The established circulatory organ culture for testis explants of the Nile tilapia allowed examining the effect of tilapia pituitary extract (tilPE) and human chorionic gonadotropin (hCG) on this tissue. The experimental flow-through setup described in this work provides the possibility to study the function of the male tilapia gonads on a cellular and transcriptional level for at least seven days. After one week of culture, tilapia testis slices kept their structure and all stages of spermatogenesis could be detected histologically. Without gonadotropin supplementation however, fibrotic structures appeared, whereas addition of tilPE preserved spermatogenic cysts and somatic interstitium completely. We could show that tilPE has a stimulatory effect on spermatogonia proliferation in our culture system. In the presence of tilPE or hCG, the gene expression of steroidogenesis related genes (cyp11b2 and stAR2) were notably increased. Other testicular genes like piwi1, amh or dmrt were not expressed differentially in the presence or absence of gonadotropins. We established a suitable system for studying tilapia spermatogenesis ex vivo with promise for future applications.